4 Acquisition of small field dosimetry data: Establishment of acquisition protocols, comparison and characterization of different detectors. (December 2018) - Assam, M.; Champoudry, J.; Benkreira, M.
Abstract : Introduction: In small fields conditions, the acquisition of dosimetry data used for beam commissioning can become a real challenge. The use or not of a reference chamber, the detectors positioning, their sizes and composition imply adapted acquisition protocols. The goal of this work is to determine acquisition parameters and positioning protocol for each detector, in order to realize a comparative analysis of their responses according to the type of acquisition. Methods: As part of this work, several detectors: MicroDiamond 60019 (PTW), Razor Diode (IBA), ionization chambers CC01 and CC04 (IBA), Stealth transmission chamber, have been used to acquire dosimetry data : beams profiles, percentage depth dose and output factor (OF). These measurements have been realized for fields ranging from 0.4 cm × 0.4 cm to 3.2 cm × 3.2 cm with a Plateform Synergy Beam Modulator Accelerator and a Blue Phantom 2 water tank (IBA). According to the type of detector, acquisition protocols are configured (resolution and integration time). Comparative measurements are achieved with and without a reference chamber (Stealth) so as to study the impact of the latter on the results. A comparison of percentage depth dose, beams profiles and OF acquired with these different detectors is realized to characterize their differences in term of response. Results: The first results show that specific positioning and acquisition protocols are necessary for each detector. The reference chamber allows to save a significant amount of time during the data acquisition without apparently perturbing the beam quality. For OF, significant differences appear among different detectors for fields inferior to 2.4 cm × 2.4 cm. Measurements are undergoing. Conclusions: Dosimetry measurements in small fields conditions require adapted acquisition parameters and precise detectors positioning. The complementarity of these detectors seems to be adapted to the dosimetry data acquisition in small fields conditions. The MicroDiamond and the Razor diode, by their conception and their small sensitive volume, seem to be the best adapted detectors for fields inferior to 1 cm × 1 cm.